2017
DOI: 10.1038/s41598-017-08899-7
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Improves Lipid Metabolism and Ameliorates Obesity by Regulating CaMKII-Mediated PDE4 Inhibition

Abstract: Our recent studies revealed that supplementation with the reduced form of coenzyme Q10 (CoQ10H2) inhibits oxidative stress and slows the process of aging in senescence-accelerated mice. CoQ10H2 inhibits adipocyte differentiation and regulates lipid metabolism. In the present study, we show that dietary supplementation with CoQ10H2 significantly reduced white adipose tissue content and improved the function of brown adipose tissue by regulating expression of lipid metabolism-related factors in KKAy mice, a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 74 publications
(74 reference statements)
4
55
0
3
Order By: Relevance
“…Importantly, resveratrol has been demonstrated to increase cAMP by inhibiting PDE4 [67]. A recent study also reported that dietary supplementation of a reduced form of coenzyme Q10 (CoQ 10 H 2 ) suppressed hepatic PDE4 expression, increased cAMP levels and fatty acid β-oxidation via the SIRT-1/PGC-1α/PPARα pathway, and inhibited the development and progression of obesity and type 2 diabetes in a mouse model [68]. The authors also reported the inhibitory effect of CoQ 10 H 2 on the genes involved in de novo lipogenesis in the liver such as SREBP1c.…”
Section: The Role Of Camp In Nafldmentioning
confidence: 99%
“…Importantly, resveratrol has been demonstrated to increase cAMP by inhibiting PDE4 [67]. A recent study also reported that dietary supplementation of a reduced form of coenzyme Q10 (CoQ 10 H 2 ) suppressed hepatic PDE4 expression, increased cAMP levels and fatty acid β-oxidation via the SIRT-1/PGC-1α/PPARα pathway, and inhibited the development and progression of obesity and type 2 diabetes in a mouse model [68]. The authors also reported the inhibitory effect of CoQ 10 H 2 on the genes involved in de novo lipogenesis in the liver such as SREBP1c.…”
Section: The Role Of Camp In Nafldmentioning
confidence: 99%
“…We next tested whether CoQ could alleviate insulin resistance in vivo by providing liposomal CoQ 10 via intraperitoneal injection every second day. CoQ 10 was used for these studies as it was not feasible to obtain sufficient CoQ 9 and the doses of CoQ 10 used in these studies were optimised so that we did not observe changes in body weight or adiposity, reported previously ( Xu et al, 2017 ), since such metabolic changes would likely directly affect insulin action in muscle and adipose. CoQ 10 administration improved whole-body glucose tolerance in mice fed a HFHSD for 5 or 14 d ( Figure 4D–E , Figure 4—figure supplement 1F–G ) without altering insulin secretion ( Figure 4F , Figure 4—figure supplement 1H ).…”
Section: Resultsmentioning
confidence: 99%
“…Ma et al also showed that treatment of baicalin, a flavone, causes an increase in [Ca 2+ ]i concentration at the similar amount to our result, which activated CaMKKβ in LKB1 deficient HeLa and A549 cell line 33 . In contrast, increased [Ca 2+ ]i can also activate other protein kinases, which potentially affect apoptosis and autophagy of GECs and podocytes related to endoplasmic reticulum stress and mitochondrial dysfunction, such as calcium/calmodulin dependent protein kinase II 34 . The precise mechanism underlying CaSR upregulation by cinacalcet and subsequent CaMKKβ/LKB1 activation is not completely understood.…”
Section: Discussionmentioning
confidence: 99%